Remote Access Tools and DBMS for Modernising Research Libraries - V, Thangavel (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Library services are being redefined by the incorporation of digital resources, which allow for innovation in everything from programming and collections to patron interaction and operational efficiency. Libraries' continued adoption of these technologies strengthens their position as forward-thinking, dynamic organisations, guaranteeing that their services continue to be significant and relevant in a quickly changing digital environment. This study,